The traditional pain easing methods [Aǧri geçirmede kullanilan geleneksel yöntemler] - (:unkn) unknown (My University, 2003)
The objective of this study is to define the traditional pain easing approaches of adult individuals. The scope of the research was composed of individuals between ages 18-65 living in the central section of Erzincan. The results of the pain prevalance were used as the base in evaluating the examplification capacity and 800 individuals were included in the study. The results of the research revealed that 65.6% of them had acute pain experiences. When the dispersion of the pain according to the body parts was examined, it was seen that headache was the most common pain with a 43.9% percentage. It was also defined that, among the traditional methods to release the pain, exercising was the most common (53.4%) followed by hot applications (47.6%), redirection of thoughts away from the pain (22.3%) and other minor methods including herbals, massage, religious beliefs, methods related with animal products and cold applications. As a result, it was defined that the traditional methods were commonly used.
Keywords: Pain; Traditional; Treatment